Optimalisasi Open Banking pada Layanan Keuangan Digital dalam Penegakan Rezim Anti Pencucian Uang - Rusli, Ganda Raharja; Fermay, Anestia Hayubriandini (Pusat Pelaporan dan Analisis Transaksi Keuangan (PPATK), 2024)
Technology has revolutionized finance, but seamless services increase fraud risks. As digital finance grows, anti-money laundering (AML) systems struggle with high transaction volumes. The main objective of this study is to verify whether open banking catalyzes the efficiency of transaction monitoring in AML. Another objective is to analyze the current agenda of regulators in Indonesia, which is related to the Indonesia Payment Systems Blueprint 2025 and customer data security. The Delphi technique pinpointed contemporary AML compliance technologies, encompassing money laundering, Regulatory Technology, and regulatory bodies. The article delves into a comparative analysis between Regulatory Technology and financial crime, which emphasizes several actions to eradicate money laundering, such as strengthening the AML system, customer screening, and allowing cross-data sharing between institutions. In addition, this paper explores RegTech's limitations and forthcoming hurdles regarding AML compliance. The finding shows that open banking catalyzes the efficiency of transaction monitoring in AML and supports the regulator's agenda to combat money laundering with some requirements.